Tuning Domain Wall Oscillation Frequency in Bent Nanowires Through a Mechanical Analogy - Altbir-Drullinsky, D (Institute of Physics, 2024)
In this work, we present a theoretical model for domain wall (DW) oscillations in a curved magnetic nanowire with a constant curvature under the action of a uniaxial magnetic field. Our results show that the DW dynamics can be described as that of the mechanical pendulum, and both the NW curvature and the external magnetic field influence its oscillatory frequency. A comparison between our theoretical approach and experimental data in the literature shows an excellent agreement. The results presented here can be used to design devices demanding the proper control of the DW oscillatory motion in NWs. © 2023 IOP Publishing Ltd.